(untitled) (International Journal of Engineering and Computer Science, 2015)
MANETs are being widely used and it is the technology that is attracting a large variety of applications. Routing in MANETs is considered a challenging task due to the unpredictable changes in the network topology, resulting from the random and frequent movement of the nodes and due to the absence of any centralized control. Efficient routing protocols can provide significant benefits to mobile Ad-Hoc networks in terms of both performance and reliability. In this paper, we evaluate the performance of two reactive routing protocols, Ad hoc On demand Distance Vector (AODV) and Dynamic Source Routing (DSR). The major goal of this study is to analyze the performance of well known MANETs routing protocol in random mobility case. Hence it becomes important to study the impact of mobility on the performance of these routing protocols. The simulation has done in NS-2 simulator and the performance is analyzed with respect to performance matrices like Average End-to-End Delay, Normalized Routing Load (NRL), Packet Delivery Fraction (PDF), and Throughput and also measures the performance of TCP and UDP packets. Simulation results verify that AODV gives better performance as compared to DSR